Mecanismele legale de protecție a drepturilor omului la un mediu sănătos [Articol] - Punga, Irina; Iordanov, Iordanca-Rodica (CEP USM, 2021)
The protection of the human right to a healthy environment cannot be achieved in the absence of legal and effective mechanisms in place, that would regulate it. Mechanisms responsible for the protection of the right to a healthy invironment/environmental matters do not only guarantee the assurance and possibility of exercising such rights, but also constitute an important procedural right on its own. Environmental issues will largely trigger the proper functioning of the mechanisms set to protect the human rights to a healthy environment, which will alternatively completely eliminate the problem of access to justice in environmental matters. The article includes a study dedicated to the identification and assessment of the particularities of the legal mechanism for the protection of ecological rights and interests, including the national, international legislation and the practice of ECHR.
LEGAL MECHANISM FOR THE PROTECTION OF THE HUMAN RIGHT TO A HEALTHY ENVIRONMENT
Keywords: right to a healthy environment; legal mechanism; access to justice; extrajudicial proceeding; mediation; ombudsman